Islamist Social Movement of Hamas Regarding Israel’s Attack on Gaza from the Perspective of Critical Theory - Idrus, Muh Rizky Hikmatullah; Purnama, Chandra; Hermawan, Yulius Purwadi (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to analyze how Hamas as Islamist Social Movement reviewed from the perspective of Critical Theory of International Relations Studies. The theories used in this study are the concept of Critical Theory and Social Movement Theory. The research method is a descriptive qualitative method, with a case study approach model. Data collection techniques are carried out through literature reviews from various online news, documents, books and journals related to the research topic. The results indicate that Hamas movement is formed by historical structures, consist of material capabilities with organizational capabilities. Ideas by the desire to fight against Israel occupation and institutionalized by supporting of Palestinian. So, social forces with Hamas' ideology and response to Fatah's approach, made Hamas takes different way in responding to the Israeli occupation. In addition, Western media coverage of Hamas has created a negative image of it so creating biased facts.